A survey of optometric contact lens prescribing in Malaysia - Norhani Mohidin; Tee, Lee Fung (Penerbit UKM, 2009)
This survey represents an initial examination of contact lens practice in Malaysia. It is based on a questionnaire that was sent to selected members of the Association of the Malaysian Optometrists to survey the prescribing habits of g contact lenses and care products. Questions included types of lenses prescribed, care systems frequently recommended and types of complications seen. Optometrists in Malaysia prescribed an average of 90 new pairs of contact lenses per year. Soft lenses made up 84% of the prescription followed by 14% of rigid gas permeable lenses and 1.5% of polymethymethacrylate lenses. Disposable/frequent replacement lenses accounted for 60% of the soft lenses prescribed. The most commonly prescribed disinfecting system was chemical disinfection. The most common complication seen during aftercare consultation was dry eye-related problems.